PENTINGNYA PENERAPAN MANAJEMEN DALAM ORGANISASI (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
An organization is a social unit consisting of two or more people, which is consciously coordinated and functions on a relatively continuous basis to achieve one or a series of goals. Organizations are closely related to management and work procedures because the organization as a whole requires management to regulate the work system. Where management has a very important role in the success of an organization in achieving its goals. Management is a process of planning, organizing, leadership and supervision in an organization that is carried out systematically to achieve certain goals. This service aims to increase knowledge about management science, especially management which is used to manage administrative activities in organizations. so it is hoped that it can help in organizing reports properly and improving their performance. Strategic plan by increasing public awareness of the importance of applying management science in organizations so that it can be used as consideration for the community in overcoming problems that occur in the surrounding environment.